2009
DOI: 10.1111/j.1574-6941.2008.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrient status and grazing pressure on the fate of Francisella tularensis in lake water

Abstract: The natural reservoir of Francisella tularensis, the causative agent of tularaemia, is yet to be identified. We investigated the possibility that Francisella persists in natural aquatic ecosystems between outbreaks. It was hypothesized that nutrientrich environments, with strong protozoan predation, favour the occurrence of the tularaemia bacterium. To investigate the differences in adaptation to aquatic environments of the species and subspecies of Francisella, we screened 23 strains for their ability to surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…Thelaus et al found that F. tularensis subsp. holarctica had increased resistance to both ciliate and flagellate protozoa compared to that of E. coli (71). Although the role of biofilm formation in resistance to predation was not addressed, this observation suggests that F. tularensis may actively prevent protozoal grazing in nature.…”
Section: Figmentioning
confidence: 81%
“…Thelaus et al found that F. tularensis subsp. holarctica had increased resistance to both ciliate and flagellate protozoa compared to that of E. coli (71). Although the role of biofilm formation in resistance to predation was not addressed, this observation suggests that F. tularensis may actively prevent protozoal grazing in nature.…”
Section: Figmentioning
confidence: 81%
“…The ciliate was much more efficient in degrading the bacteria than the flagellate, but the same trend in mortality rate of 'edible' and 'inedible' bacteria, was observed, i.e. the degradation ratio between the edible and the inedible bacteria remained constant, regardless of the predator (Thelaus et al 2009). We therefore think that the relative change in edibility would have been similar if another bacterivore had been used.…”
Section: Discussionmentioning
confidence: 66%
“…In a study by Thelaus et al (2009), the consumption rates of different bacteria by the same ciliate as used in this study (T. pyriformis) and an interception feeding flagellate (Ochromonas danica) were compared. The ciliate was much more efficient in degrading the bacteria than the flagellate, but the same trend in mortality rate of 'edible' and 'inedible' bacteria, was observed, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that F. tularensis survives in bacterivorous amoebae, ciliates, and nanoflagellates, suggesting protists may play a role in the environmental survival of Francisella spp. (Abd et al 2003, Thelaus et al 2009). Also, a novel F. noatunensis subspecies, Candidatus F. noatunensis subsp.…”
Section: Discussionmentioning
confidence: 99%